Accounting for L2 learners’ errors in word stress placement - Karjo, Clara Herlina (Indonesian Journal of Applied Linguistics, 2016)
Stress placement in English words is governed by highly complicated rules. Thus, assigning stress correctly in English words has been a challenging task for L2 learners, especially Indonesian learners since their L1 does not recognize such stress system. This study explores the production of English word stress by 30 university students. The method used for this study is immediate repetition task. Participants are instructed to identify the stress placement of 80 English words which are auditorily presented as stimuli and immediately repeat the words with correct stress placement. The objectives of this study are to find out whether English word stress placement is problematic for L2 learners and to investigate the phonological factors which account for these problems. Research reveals that L2 learners have different ability in producing the stress, but three-syllable words are more problematic than two-syllable words. Moreover, misplacement of stress is caused by, among others, the influence of vowel lenght and vowel height.